Evaluating academic development in the higher education sector: academic developers' reflections on using a toolkit resource. Issue 7 (10th November 2017) - Winter, Jennie; Turner, Rebecca; Spowart, Lucy; Muneer, Reema; Kneale, Pauline
ABSTRACT: The professionalisation of teaching is of increasing importance in UK higher education due to converging processes including the proliferation of managerialism, increasing quality agendas and changes to student fee structures. These have brought into sharp relief the need for greater understanding of how quality teaching evolves in university settings. One key element of this involves academic development and its impacts on teaching and learning. Current literature suggests that a plethora of ideas, frameworks and instruments claiming best practice exist but that take-up of these is inconsistent. This prompted a UK national research project which produced an evidence-based toolkit for evaluating academic development. As part of the toolkit augmentation, academic development representatives from across the sector were asked to create, review and test uniquely tailored evaluation instruments. These instruments were then piloted on university teachers who had participated in teaching-related continuing professional development activities. This paper reports on these individuals' reflections of using the toolkit. It suggests that academic developers are interested in evaluating the impact of their work on teachers, students and on the wider institutional culture but that confidence and expertise varies. Using the toolkit generated 'traditional' evaluation data including satisfaction with the development activity and changes to lecturers' conceptions and behaviours. However, it also prompted critical discussions around current evaluation practice. This included the need for transformational reform of institutional culture to support links between evaluation and good standing; and making explicit the thorny issue of evidencing student learning. This paper will be of interest to those with an interest or responsibility for evaluating teaching in higher education. The paper offers an important contribution to the international literature at a time when global higher education is faced with questions about teaching, learning and quality. Evaluation, and how to do it well, is timely and important business.